Increased skeletal muscle mitochondrial free radical production in peripheral arterial disease despite preserved mitochondrial respiratory capacity. Issue 6 (8th May 2018) - Hart, Corey R.; Layec, Gwenael; Trinity, Joel D.; Kwon, Oh Sung; Zhao, Jia; Reese, Van R.; Gifford, Jayson R.; Richardson, Russell S.
Abstract : New Findings: What is the central question of this study? What is the degree to which skeletal muscle mitochondria‐derived reactive oxygen species (ROS) production is linked to impaired skeletal muscle function in patients with early‐stage peripheral arterial disease (PAD) and what is the impact on mitochondrial respiratory capacity? What is the main finding and its importance? This is the first study to document increased mitochondria‐derived reactive oxygen species production associated with elevated intramuscular oxidative stress, despite preserved mitochondrial respiratory function, in patients with PAD. Furthermore, systemic inflammation, mitochondria‐derived ROS production and skeletal muscle oxidative stress were strongly correlated to disease severity, as indicated by ankle‐brachial index, in patients with PAD. Abstract: Skeletal muscle mitochondrial dysfunction, which is not fully explained by disease‐related arterial occlusion, has been implicated in the pathophysiology of peripheral arterial disease (PAD). Therefore, this study comprehensively assessed mitochondrial respiratory function in biopsies from the gastrocnemius of 10 patients with PAD (Fontaine Stage II) and 12 healthy controls (HC). Intramuscular and systemic inflammation, mitochondria‐derived reactive oxygen species (ROS) production, and oxidative stress were also assessed to better understand the mechanisms responsible for the proposed PAD‐induced mitochondrial dysfunction. Interestingly, mitochondrial respiratory capacity, assessed as complex I (CI) and complex II (CII)‐driven State 3 respiration, measured separately and in combination (State 3 CI+II), revealed no difference between the patients with PAD and the HC. However, mitochondria‐derived ROS production was significantly elevated in PAD (HC: 1.0 ± 0.9; PAD: 4.3 ± 1.0 AU (mg tissue) −1 ). Furthermore, patients with PAD exhibited significantly greater concentrations of the pro‐inflammatory markers tumour necrosis factor α in plasma (HC: 0.9 ± 0.4; PAD: 2.0 ± 0.3 pg ml −1 ) and interleukin 6 in both plasma (HC: 2.3 ± 0.4; PAD: 4.3 ± 0.5 pg ml −1 ) and muscle (∼75% greater). Intramuscular oxidative stress, assessed by protein carbonyls and 4‐hydroxynonenal, was significantly greater in PAD compared to HC. Ankle brachial index was significantly correlated with intramuscular inflammation, oxidative stress and mitochondria‐derived ROS production. Thus, elevated intramuscular inflammation, oxidative stress and mitochondria‐derived ROS production are likely to contribute to the pathophysiology of the skeletal muscle dysfunction associated with PAD, even in the presence of preserved mitochondrial respiratory function in this population. Abstract :